2020
DOI: 10.2139/ssrn.3537612
|View full text |Cite
|
Sign up to set email alerts
|

Does Private Equity Investment in Healthcare Benefit Patients? Evidence from Nursing Homes

Abstract: The past two decades have seen a rapid increase in Private Equity (PE) investment in healthcare, a sector in which intensive government subsidy and market frictions could lead high-powered forprofit incentives to be misaligned with the social goal of affordable, quality care. This paper studies the effects of PE ownership on patient welfare at nursing homes. With administrative patient-level data, we use a within-facility differences-in-differences design to address nonrandom targeting of facilities. We use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…One of these studies, 9 in addition to 3 others, 20 , 21 , 22 examined PE ownership and nursing home staffing levels; 3 studies 9 , 20 , 21 found little evidence of changes in staffing and 1 study 22 identified declines in staffing. Two recent working papers 3 , 15 also had mixed results. The first 15 found PE ownership to be associated with declines in staffing levels, increased rehospitalization rates, and worse CMS Five Star Ratings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of these studies, 9 in addition to 3 others, 20 , 21 , 22 examined PE ownership and nursing home staffing levels; 3 studies 9 , 20 , 21 found little evidence of changes in staffing and 1 study 22 identified declines in staffing. Two recent working papers 3 , 15 also had mixed results. The first 15 found PE ownership to be associated with declines in staffing levels, increased rehospitalization rates, and worse CMS Five Star Ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent working papers 3 , 15 also had mixed results. The first 15 found PE ownership to be associated with declines in staffing levels, increased rehospitalization rates, and worse CMS Five Star Ratings. Conversely, the second working paper 3 found that PE firms tended to increase staffing levels and improve the Five Star Ratings of nursing homes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, they believe that there exists a tradeoff between 'efficiency' (which is taken to mean the 'maximization' of real GDP) and 'equity' (which refers to how GDP is distributed). 17 If the trade-off holds, a more unequal distribution of 15 Recent research by Gupta et al (2021) shows that private-equity (PE) ownership increases the shortterm mortality of Medicare patients by 10%, implying 20,150 lives lost due to PE ownership over the 12-year period of investigation. This is accompanied by declines in other measures of patient wellbeing, such as lower mobility, while taxpayer spending per patient episode increases by 11%.…”
Section: The Toxic Obsession With the Equity-efficiency Trade-offmentioning
confidence: 99%